Structural basis for a novel mechanism of DNA bridging and alignment in eukaryotic DSB DNA repair. (11th March 2015) - Gouge, Jérôme; Rosario, Sandrine; Romain, Félix; Poitevin, Frédéric; Béguin, Pierre; Delarue, Marc
Abstract Eukaryotic DNA polymerase mu of the PolX family can promote the association of the two 3′‐protruding ends of a DNA double‐strand break (DSB) being repaired (DNA synapsis) even in the absence of the core non‐homologous end‐joining (NHEJ) machinery. Here, we show that terminal deoxynucleotidyltransferase (TdT), a closely related PolX involved in V(D)J recombination, has the same property. We solved its crystal structure with an annealed DNA synapsis containing one micro‐homology (MH) base pair and one nascent base pair. This structure reveals how the N‐terminal domain and Loop 1 of Tdt cooperate for bridging the two DNA ends, providing a templating base in trans and limiting the MH search region to only two base pairs. A network of ordered water molecules is proposed to assist the incorporation of any nucleotide independently of the in trans templating base. These data are consistent with a recent model that explains the statistics of sequences synthesized in vivo by Tdt based solely on this dinucleotide step. Site‐directed mutagenesis and functional tests suggest that this structural model is also valid for Pol mu during NHEJ.